Perbandingan Stabilitas Nanopartikel Erithropoietin dalam Asam Klorida dan Phospate Buffer Saline - Nuryanti, Nuryanti; Nugroho, Akmad Kharis; Martien, Ronny; Julia, Madarina (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2022)
Abstract: The erythropoietin nanoparticle system is formed from the interaction of the positive charge of chitosan and the negative charge of pectin under acidic conditions, so the stability of the nanoparticle system in hydrochloric acid and phosphate buffer Salin (PBS) is critical parameter in the choice of permeation medium. This study aimed to compare the stability of the erythropoietin nanoparticle system in HCl pH 1.2 and PBS pH 7.4. This research is an experimental laboratory study that analyzes includes the analysis of erythropoietin released from the nanoparticle system dissolved in HCl pH 1.2 and PBS pH 7.4 using spectrophotometric methods. Erythropoietin levels were calculated as free from the nanoparticle system at 15, 30, 45, 60, 90, 120, 180, and 240 minutes. Erythropoietin levels released from the erythropoietin nanoparticle system at 15 minutes in HCl medium pH 1.2 lower at 33, 63%, compared to PBS medium at pH 7.4 with free erythropoietin content of 50.85%. However, after 240 minutes the concentration of free erythropoietin from the nanoparticle system was higher in the PBS medium at pH 7.4 (60.49%) than in HCl medium at pH 1.2 (57.85%). The results showed that the erythropoietin nanoparticle system was more stable in HCl medium pH 1.2 than in PBS pH 7.4.